Vitamin D metabolism in growing pigs: influence of UVB irradiation and dietary vitamin D supply on calcium homeostasis, its regulation and bone metabolism. (19th June 2017) - Kolp, E.; Wilkens, M. R.; Pendl, W.; Eichenberger, B.; Liesegang, A.
Summary: The aim of this study was to prove whether pigs are able to synthesize vitamin D (vitD) in the skin and to investigate the influence of ultraviolet irradiation (UVB) on vitD status and calcium (Ca) homeostasis of growing pigs. Thirty‐two 11‐week‐old pigs were kept without access to sunlight and divided into four groups receiving the following treatment in a 2 × 2 factorial design: (i) UVB irradiation or not and (ii) vitD in feed or not. Blood, urine and faeces were sampled every third week. In serum, vitD metabolites, Ca, phosphorus (P), magnesium (Mg) and bone markers were analysed. Digestibility of Ca, P and Mg as well as urinary excretion of these minerals was analysed. After 14 weeks, the animals were slaughtered, and samples of skin, intestines, kidneys and bones (metatarsus) were taken for further analyses: sterols of vitD synthesis in the skin, Ca flux rates in the intestines, expression of genes involved in Ca transport in the intestines and kidneys, bone mineral density (BMD) with the aid of peripheral quantitative computer tomography and bone mineral content by ashing the metatarsus. Irradiated animals showed higher levels of 7‐dehydrocholesterol and tachysterol in the skin, higher levels of 25‐hydroxycholecalciferol and 1, 25‐dihydroxycholecalciferol in the serum and higher Ca net flux rates were determined in Ussing chambers. In contrast, the expression of genes involved in Ca transport in the intestines and kidneys was not altered. Similarly, the digestibility of Ca and P as well as the urinary excretion was not affected. With respect to the metatarsus, no differences in mineral contents and BMD were found between groups. At the end of the study, some subclinical signs of beginning vitD 'insufficiency' were observed in the group without access to vitD (represented by higher expression of 1 α ‐hydroxylase in the kidney and increased parathyroid hormone in serum).